Prepartum supplementation influences response to timed artificial insemination by suckled mature beef cows - Thomas, M.D.; Stevenson, Jeffrey S.; Bolte, J.W.; Sproul, N.A.; Linden, D.A.; Olson, K. C.; Jaeger, John R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Fat supplementation before calving (i.e., prepartum) can alter reproductive performance of beef cows. These effects do not seem to be related to energy or protein content of the supplement. Chemical structures of some plant fats are similar to chemical structures of certain reproductive hormones; moreover, some fats are precursors to prostaglandin production. Prepartum vegetable fat supplementation has been associated with improved reproductive performance by cows and heifers managed for artificial insemination (AI) breeding. The biological basis for this effect is not clearly understood but is believed to reflect the influence of fat supplements on cyclicity, body weight, body condition, and other factors. Our objective was to evaluate the effects of supplementing whole fuzzy cottonseed or whole raw soybeans on pregnancy rates following ovulation synchronization and timed AI of mature beef cows.
Keywords: Beef; Cattle; Artificial insemination (AI)